(3GdMRH GdeCKhQ hGdOQ GdefKhQs - (3eMeO WjH GdGSeGA Hf CMeO Hf eMeO WjH GdGSeGA GdbGOQj GdSeGfj GdeGdcj,J (B1354 (3g` s
(3ChdgG (B:s
(3Gddge Udi Ydi SjOfG eMeO GdfHi GdCei hYdi Bdg hSde Gddge jG ef EPG JVGjbJ GdCehQ QLYJ Edjg hEPG cKQJ GdMhGFL s
(3BNQgG (B:s
(3hGZaQ dfG QHfG Efc CfJ GdYRjR GdMcje SHMGfc Gddge hJMjJge ajgG SdGe haj AGNQ OYhjge Cf GdMeO ddg QH GdYGdejf hGdeYhPJjf GfJgi s
(3hjMJhi Ydi COYjI jbhdgG GdSGFd djSJLjH dg Gddg SHMGfg hJYGdi OYhJg hjMbb eWGdHgs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3eUOQ GbJfGA GdCUd (B:s
(3GdShOGf (B_ (3jhfSch s
Keywords: (3GdJUha hGdBOGH GdTQYjIs